Evaluation of pre-treatments for shelf life extension of minimally processedfenugreek (Trigonella foenum graecum L.) - Kozhummal, Ranjitha; Sudhakar Rao DV; Mhasizotuo; Vasudeva; Shivashankara K S (Journal of Horticultural Sciences, 2025)
Potential of different pretreatments for shelf life enhancement and nutritional quality maintenance in minimally processed fenugreek (Trigonella foenum-graecum) leaves (MPFL) at 8°C storage were evaluated. Pretreatment agents such as calcium propionate, calcium chloride, kinetin, gibberellic acid, 1-methyl cyclo propene, neutral electrolysed water and sodium hypochlorite were used. The results have proven that a five minutes dip in kinetin solution (50 mg L-1) was the best among all tested pretreatments; and it resulted in achieving eight days shelf life compared to four days in control samples. Besides this, better maintenance of total antioxidants (1735 mg ascorbic acid equivalent antioxidant capacity kg-1) and proteins (44 g kg-1), at levels close to that of fresh leaves, could be achieved. Calcium propionate (1.5 g L-1) was identified as the second best treatment. It was also shown that minimally processed fenugreek leaves (MPFL) is a rich source of vitamins B1, B2, E and K. The B vitamins were susceptible to deterioration during storage, while their loss could be minimized with kinetin treatment. Sanitizers like chlorine (100 mg L-1 available chlorine) and neutral electrolysed water (100 and 200 mg L-1) have reduced the shelf life of MPFL indicating their phytotoxicity to FL. The results of the study open up the possibility of using kinetin as an effective pretreatment tool for MPFL in minimal processing industry.
Keywords: Calcium chloride; fenugreek leaves; kinetin; minimal processing; pretreatment; sanitizer